Endophytes as Permanent or Temporal Inhabitants of Different Ecological Niches in Sustainable Agriculture - Agnieszka Kuźniar; Anna Kruczyńska; Kinga Włodarczyk; Jaco Vangronsveld; Agnieszka Wolińska (Applied Sciences)
Local adaptation of plants to environmental conditions is gaining attention, particularly in the context of climatic change and the microbiota that are associated with it. It should be noted that endophytes play a large role in shaping plants. These are microorganisms that reside within plant tissues without causing any apparent harm to their host. It should also be highlighted that endophytes play an essential role in ecosystems by contributing to plant health through multiple mechanisms. We suggest that endophytes affect some animals, as they are used in the ecological niche in which animals thrive. Thus, we analyzed this aspect of endophytes as persistent but impermanent inhabitants of various ecological niches. Therefore, the aim of the current review is to present the knowledge (from the last 10 years) on plant endophytes, their applicability in agriculture and endophytes affecting animals. We focused on bioproducts and biofertilizers containing endophytes, which are indirectly connected with agrobiotechnology, and the legal conditions associated with the marketing of these products, which also impact some animals, as they are used in the ecological niche in which animals thrive.